2019
DOI: 10.2166/wst.2019.403
|View full text |Cite
|
Sign up to set email alerts
|

Development and adoption of wastewater treatment system for peri-urban agriculture in Multan, Pakistan

Abstract: The present research was conducted to assess the feasibility of biological treatment of a typical wastewater (WW) stream in Multan, Pakistan, using daily trends of WW characteristics and to design a wastewater treatment (WWT) system for that stream. The pH (5.8–6.2), temperature (24–30 °C), biological oxygen demand (BOD5: 128–265 mg/L), ultimate BOD (BODu: 227–438 mg/L), BOD/total Kjeldahl nitrogen (BOD5/TKN:5.9–11.2), BODu/BOD5 (1.6–2.0), carbonaceous BODu/nitrogenous BODu (CBODu/NBODu:1.6–2.8) of the WW was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The influent pH was observed between 7.2 ± 1.8 to 8.1 ± 0.2 while the effluent pH ranged from 6.9 ± 1.7 to 7.9 ± 0.3. The obtained pH range indicated the feasibility of good biological treatment, effective nitrification and optimum operation of trickling filter (Kanwar et al 2019;Khan et al 2019a, b).…”
Section: Tn and Tp Removalmentioning
confidence: 83%
See 2 more Smart Citations
“…The influent pH was observed between 7.2 ± 1.8 to 8.1 ± 0.2 while the effluent pH ranged from 6.9 ± 1.7 to 7.9 ± 0.3. The obtained pH range indicated the feasibility of good biological treatment, effective nitrification and optimum operation of trickling filter (Kanwar et al 2019;Khan et al 2019a, b).…”
Section: Tn and Tp Removalmentioning
confidence: 83%
“…As cascade aeration is considered as the simple, zero-energy demanding and having less maintenance cost. So, the power consumption of both CTF and CCTF was estimated as 0.3-0.6 kWh/m 3 that was found considerably less than for anaerobic (0.03-3.572 kWh/m 3 ) and aerobic (2 kWh/ m3) membrane bioreactors (Martin et al 2011;Rasool et al 2017;Kanwar et al 2019). The power consumption of CTF and CCTF is generally related to the pumping and recirculation that can be decreased by constructing the systems on a slope.…”
Section: Application Of Bod Reaction Kinetic Modelmentioning
confidence: 98%
See 1 more Smart Citation
“…DO concentration above 1 mg/L is essential for the nitrification process, whereas with low concentrations, both ammonia-oxidizing bacteria (AOB) and nitrite-oxidizing bacteria (NOB) growth rates are reduced (Ma et al, 2016;Wang et al, 2021). In the present treatment system, the natural ventilation through the aeration During the operating period, the pH of the influent varies between 7.2 and 8.5, which is within the optimum range for proper biological treatment and effective nitrification (Kanwar et al, 2019;Khan et al, 2019). The pH of treated UWW decreased significantly (pH = 6.5-7.4), indicating normal biological nitrification inside the trickling filter.…”
Section: Ph Do and Temperaturementioning
confidence: 93%
“…Kanwar et al (2022) found that the power consumption of both conventional and cascade cum trickling filters was in the range of 0.3-0.6 kWh/m 3 . m 3 ) membrane bioreactors (Garfí et al, 2017;Kanwar et al, 2019;Martin et al, 2011). The power consumption of the developed trickling filter is only related to the pumping and recirculation of water.…”
Section: Energy Consumption For Tuww Reusementioning
confidence: 99%